Leadership styles of Iranian Physical Education teachers - Houshyar, M.; Hamid-Sajadi, S.; Amirtash, A.; Haji-Anzahaei, Z. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The present study aimed to determine the most adequate leadership style for Iranian Physical Education teachers. The sample was composed of 384 Physical Education teachers from Iran of 4 regions and 20 provinces. Multistage sampling and simple random sampling were used. The variables studied in this research were: 1) Leadership style. 2) Sociocultural attitudes. 3) Personality dimensions. 4) Situational factors. The leadership style was evaluated with the Likert Leadership Styles Standard Questionnaire. The sociocultural attitudes of the physical education teachers were determined with the Cultural Attitudes Questionnaire. The personality traits of the educators were analysed with the Five Personality Trait Inventory. The situational factors of employees were assessed with the Standard Staff Readiness Questionnaire. The final model of the appropriate leadership style with personality traits, cultural attitudes and situational factors of Physical Education teachers indicates that the most appropriate leadership styles for the Iranian Physical Education teachers were Delegating and Coaching styles, followed by Supporting and Directing styles.